EXPERIMENTAL AND NUMERICAL STUDY ON THE RISE OF BUBBLES IN THE VERTICAL WATER CHANNELS - Sannan Aziz; K. Akhtar; Nadeem Ur Rehman; Mohsin Ali (Spectrum of Engineering Sciences, 2025)
This work investigates in 2D & 3D both numerically and experimentally the behavior of the rising air bubbles i.e. path and motion in three distinct vertical water channels by using a submerged needle and the impact of water channel size on the behavior of rising air bubbles and contrasts this current 3D study with the earlier 2D studies. Experimental investigations both (3D & 2D) results were taken by installing two high speed digital cameras (HSC’s). For very low flow rates, the bubbles trajectories has been observed to be spiral rather than rectilinear. The volume of fluid (VOF) approach is used for numerical analysis to investigate the trajectory of air bubbles in three different sizes of water channels. The bubbles trajectories of the front (x-y) plane and superimposed view of the (y-z) plane recorded during experimental investigations are drawn using MATLAB and then graphical representations are drawn in MS EXCEL. The bubbles did not rise straight; instead, they rose in spiraled. The numerical and experimental results agreed with one another. Water channel size has no effect on the behavior of rising air bubbles.